2001
DOI: 10.1254/jjp.85.376
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Potentiates Steroidogenic Effect of Adrenocorticotropic Hormone in Bovine Adrenocortical Fasciculata Cells

Abstract: ABSTRACT-We examined the effect of extracellular adenosine 5'-triphosphate (ATP) on adrenocorticotropic hormone (ACTH)-and angiotensin II-induced steroidogenesis in bovine adrenocortical fasciculata cells. The low concentration of ATP (5 mM) potentiated ACTH-induced steroidogenesis synergistically. However, the purine derivative did not affect angiotensin II-induced steroidogenesis. Although adenosine (100 mM) (a metabolite of ATP) showed a weak steroidogenic effect, it did not potentiate ACTH-induced steroido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…AngII is known to act on AT 1 receptors expressed in BAFC [10]. AT 1 is also known to be coupled to G q protein activation, resulting in Ca 2+ release from intracellular stores [23], [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AngII is known to act on AT 1 receptors expressed in BAFC [10]. AT 1 is also known to be coupled to G q protein activation, resulting in Ca 2+ release from intracellular stores [23], [24].…”
Section: Resultsmentioning
confidence: 99%
“…This dominance of P2 over P1 for steroidogenesis is different from that seen in rats. Furthermore, BAFC are unique in that low concentrations of extracellular ATP, at levels that have no steroidogenic effect alone, enhance ACTH-induced glucocorticoid secretion synergistically [10]. Thus the P2 receptors expressed on adrenocortical cells may have something to do with defense systems under stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, extracellular nucleotides also have potent steroidogenic effects in BAFC (Hoey et al, 1994;Kawamura et al, 1991;Nishi, 1999;Nishi et al, 2002). Besides their own effects, Kawamura et al reported that extracellular nucleotides enhance the steroidogenic effects of ACTH synergistically in BAFC (Kawamura et al, 2001). That is, nucleotides cause both their own steroidogenic effects and the modulation of ACTH effects.…”
Section: Discussionmentioning
confidence: 99%
“…ATP also potentiates the steroidogenic effect of ACTH in bovine fasciculate cells (Kawamura et al, 2001). In addition to ATP, ADP and uridine triphosphate stimulate calcium signaling and cortisol secretion (Hoey et al, 1994), ADP may also act through G s -coupled P2YRs (Nishi et al, 2002), and ATPγS stimulates both inositol phosphate production and cAMP accumulation (Nishi et al, 2004), suggesting a role of more than one P2R subtype in purinergic regulation of steroidogenesis in adrenocortical cells (Fig.…”
Section: Purinergic Regulation Of the Hypothalamic-pituitary Adrenmentioning
confidence: 99%